1988
DOI: 10.1002/j.1537-2197.1988.tb13457.x
|View full text |Cite
|
Sign up to set email alerts
|

Equations for the Motion of Airborne Pollen Grains Near the Ovulate Organs of Wind‐pollinated Plants

Abstract: A technique is presented that is capable of predicting the motion of airborne pollen grains and the probability of pollen capture by wind‐pollinated plants. Equations for the motion of rigid‐walled particles (= pollen grains, spores, or Sephadex beads) in a supporting, compressible fluid (= air) are derived from the first principles of fluid dynamics. These equations are incorporated into a computer program (MODEL) which can be used with a desktop computer. The operation of MODEL requires empirical data on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…The results of both our aggregation and staking experiments confirm Niklas's (1987, 1988) hypothesis that diffuse and compact grass inflorescences rely on contrasting aerodynamic mechanisms to effect pollination. This conclusion is further supported by comparison of the proportion of pollen removed from anthers that reaches stigmas (pollen‐transfer efficiency).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of both our aggregation and staking experiments confirm Niklas's (1987, 1988) hypothesis that diffuse and compact grass inflorescences rely on contrasting aerodynamic mechanisms to effect pollination. This conclusion is further supported by comparison of the proportion of pollen removed from anthers that reaches stigmas (pollen‐transfer efficiency).…”
Section: Discussionsupporting
confidence: 83%
“…Instead, different architectures must be alternate means of manipulating airflow. For example, Niklas’ (1987; 1988) studies demonstrated that at low airspeeds (10–50 cm s −1 ) a compact panicle ( Setaria geniculata ) captured more pollen by sedimentation than by direct inertial collision, as pollen grains aggregated on the leeward side of the inflorescence, where they recirculated. In contrast, a diffuse panicle ( Agrostis hiemalis ) captured pollen only by direct inertial collision.…”
Section: Introductionmentioning
confidence: 99%
“…In certain grasses, the large diameter of compact inflorescences appears counter‐adaptive for a structure intended for collecting particles by impaction on its windward surfaces and, therefore, it has been proposed that it functions instead as a recirculatory collector (Niklas 1987; Friedman & Harder 2005). Like previous studies that used stroboscopic photography (Niklas 1987, 1988) and fluid dynamic models (Niklas 1988) to investigate the leeward eddy of grass inflorescences, our study demonstrates leeward recirculation by pollen; in both of the grass species that we investigated, pollen accumulated on wire probes placed in the leeward eddy of a compact inflorescence exposed to oncoming airborne pollen in a wind tunnel and our CFD analyses visualized this leeward recirculation.…”
Section: Discussionsupporting
confidence: 63%
“…The lack of convergence among grasses on a single ideal form for the flowering stem suggests that various combinations of floral and inflorescence traits confer equivalent pollination success (Friedman & Harder 2005). Our study suggests that compact inflorescences, like diffuse inflorescences (Niklas 1988; Friedman & Harder 2005), accumulate pollen by impact collection. Given that the collection efficiency of an object is approximately inversely proportional to its diameter in the size range of grass inflorescences (Paw U & Hotton 1989), how can large and small diameter inflorescences have equivalent performance as pollen receptors?…”
Section: Discussionmentioning
confidence: 66%
“…Tall species expose their anthers to the faster airspeeds needed to remove large grains, because windspeed increases with elevation above the ground (Campbell, 1977). The tendency of large stigmas to deflect more air would be less disadvantageous for species with large pollen, both because the higher momentum of large grains makes them more likely to break free of deflected airstreams and collide with a stigma and because the higher settling velocity of large grains increases their sedimentation in eddies on the downstream side of stigmas (see Niklas, 1988). However, the positive relation between pollen size and both the number and total volume of pollen per floret indicates that species with large pollen invest more in pollen than species with small pollen (recall that all grasses produce one ovule per ovary).…”
Section: Possible Functional Differences Between Floret Size-infloresmentioning
confidence: 99%